Controlling the Mdm2-Mdmx-p53 Circuit - David L. Waning; Jason A. Lehman; Christopher N. Batuello; Lindsey D. Mayo (MDPI AG, 2010)
The p53 tumor suppressor is a key protein in maintaining the integrity of the genome by inducing either cell cycle arrest or apoptosis following cellular stress signals. Two human family members, Mdm2 and Mdmx, are primarily responsible for inactivating p53 transcription and targeting p53 protein for ubiquitin-mediated degradation. In response to genotoxic stress, post-translational modifications to p53, Mdm2 and Mdmx stabilize and activate p53. The role that phosphorylation of these molecules plays in the cellular response to genotoxic agents has been extensively studied with respect to cancer biology. In this review, we discuss the main phosphorylation events of p53, Mdm2 and Mdmx in response to DNA damage that are important for p53 stability and activity. In tumors that harbor wild-type p53, reactivation of p53 by modulating both Mdm2 and Mdmx signaling is well suited as a therapeutic strategy. However, the rationale for development of kinase inhibitors that target the Mdm2-Mdmx-p53 axis must be carefully considered since modulation of certain kinase signaling pathways has the potential to destabilize and inactivate p53.